Cooperação e relações de confiança : a construção da segurança e da saúde no trabalho de alto risco - Marcelle La Guardia; Francisco Lima (Universidade do Porto, 2019)
In a power distribution company, the maintenance teams at an energized network are formed by three members at least. With the reduction of the number of electricians, a study made by the engineering sector, training sector and electricians concluded that two-person services are viable. This technical group concluded that it is "technically possible" to carry out the activities this way. However, other electricians and trade union representatives say that performing the tasks in pairs will affect the employee's health and safety. The solution went through a research that placed the real work in center of the debate. Looking at activity and the intersubjective relationships has been made it possible - and this is the purpose of this article - to uncover how cooperation and trust are built up on a day-to-day basis and how they are bases for the efficiency of collective risk management in complex situations.